Variability in Capsicum Chinese Jacq - Elizabeth Cherian V (Department of Olericulture, College of Horticulture, 2000)
The research project ‘Variability in Capsicum chinense jacq’ was carried out in the College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during 1997-99. The major objective of the study were to genetically catalogue the available germplasm, to study the genetic variability, heritability, genetic gain and correlation of different characters with yield. Twenty eight accessions of C. chinense were catalogued based on the descriptor list for capsicum. Significant difference were observed for all the biometric characters studied viz, plant height, number of primary branches, days to first flowering, days to harvestable maturity, pedicel length, fruit length, fruit girth, fruit weight, number of seeds per plant, number of fruits per plant, yield per plant, driage, bacterial wilt incidence, capsaicin, oleoresin and colour value. The accession CC 8 was found to be the highest yielder during both the first (75.5g) and second (185 g) season. Accession CC 17 had the maximum average fruit weight (6.6g and 7.2g respectively during the first and second season). Number of fruits per plant was the highest in CC 37 (32.5) during the first season and CC 8 (63.5) during the second season. The accession CC 17 had the high oleoresin per cent during the first (25.75%) and second (24%) season. Accession No. CC5 observed to have the highest capsaicin percent during the first (1.85) and second (1.75%) season. During the first season bacterial wilt incidence has got the highest genotypic coefficient of variation (69.28) and phenotypic coefficient of variation (58.70) and for number of fruits per plant (gcv - 92.99, pcv - 91.72) during the second season. Fruit length recorded the highest heritability (0.993) during the first season while it was the fruit weight (0.993) during the second season. High values for genetic gain was observed for number of fruits per plant, yield, fruit weight, fruit length, bacterial wilt incidence during the first and second season. During the first season fruit length and fruit weight showed significant positive correlation with yield and the number of fruits per plant showed the significant positive correlation with yield during the second season. A selection model was formulated for C. chinense consisting of the characters yield per plant, fruit weight and number of fruits per plant. Genotypes CC8, CC5, CC37 were found to be superior during the first season and the genotypes CC8, CC23, CC10 during the second season.